Portrait of John Steinbeck - Ellwood Graham:::Creator::::::::::::
Sketch of John Steinbeck for Graham's painting which was finished in 1941. Sketch was made on Steinbeck's returned from Mexico. Artist Judith Deim (Barbara Stevenson) worked on his portrait at the same time.